PKM Pelatihan Pemasaran Dan Akuntansi Sederhana Bagi Pelaku UMKM Kecamatan Tarikolot - Nining Rahaningsih; Ade Rizki Rinaldi; Bani Nurhakim; Ahmad Rizki Fauzi; Kautsar Zidan Soleh (CV. Multi Kreasi Media, 2024)
The Tarikolot Subdistrict holds significant economic potential through micro, small, and medium enterprises (MSMEs). However, many MSME operators face challenges in managing simple marketing and accounting, which hinders their business growth. This issue arises from a lack of knowledge and skills in these areas. This Community Service Program (PKM) aims to enhance MSME operators' abilities to independently manage their marketing and accounting tasks. The methods employed include face-to-face training, group discussions, and intensive mentoring over a three-month period. The outcomes of this program are expected to improve participants' understanding of effective marketing strategies and the application of simple accounting in their business operations. The training will also enable participants to implement the acquired knowledge in their daily practices to boost efficiency and profitability.